2023
DOI: 10.3390/plants12162942
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Callus Induction and Shoot Regeneration from Tomato Cotyledon Explants

Abstract: Cultivated tomato (Solanum lycopersicum L.) is one of the most important horticultural crops in the world. The optimization of culture media for callus formation and tissue regeneration of different tomato genotypes presents numerous biotechnological applications. In this work, we have analyzed the effect of different concentrations of zeatin and indole-3-acetic acid on the regeneration of cotyledon explants in tomato cultivars M82 and Micro-Tom. We evaluated regeneration parameters such as the percentage of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…strains. Shoot induction can then be produced shortly afterwards with appropriate hormone combinations [ 90 ].…”
Section: Methods For Obtaining Gene-edited Plantsmentioning
confidence: 99%
“…strains. Shoot induction can then be produced shortly afterwards with appropriate hormone combinations [ 90 ].…”
Section: Methods For Obtaining Gene-edited Plantsmentioning
confidence: 99%
“…These phenomena represent three faces of cytokinin, which are dependent on the origin and type of auxin biosynthesis pathway. Namely, in tomato cotyledon, the “soft callus” forms mainly from mesophyll cells (direct organogenesis), and somatic embryogenesis forms from cell layers near the epidermis with the active TAA1 gene, while auxin canalization to the xylem leads to the formation of large sieve elements with further possibility of root induction after the exogenous cytokinin level is lowered [ 134 ]. However, in monocotyledon, leaf auxin transport is directed from the meristem to the leaf tips (opposite to dicotyledons), so the leaf is not able to produce endogenous auxin and, therefore, cannot react to exogenous cytokinin application.…”
Section: Major Aspects Of Plant Regenerationmentioning
confidence: 99%
“…Cotyledon has some advantages compared with leaf since it is a more standard system, while the ability of leaf regeneration is dependent on many factors that need to be considered. Cotyledon can serve as the most suitable explant for many dicotyledon species [ 134 , 180 , 181 ] because of the high capacity of auxin synthesis through the IPA pathway [ 182 ]. However, cotyledon is competent for plant regeneration only in a relatively short “window”: before the induction of shoot apical meristem.…”
Section: Major Aspects Of Plant Regenerationmentioning
confidence: 99%
“…In vitro shoot induction and multiplication is a common procedure in plant tissue culture [23]. Precise concentrations and optimal ratios of plant growth regulators (PGRs) are essential in efficiently obtaining enough shoots of high quality in vitro [19,36]. It has…”
Section: Establishment Of In Vitro Propagation Systemmentioning
confidence: 99%
“…During the past few decades, in vitro culture techniques have been explored for Jerusalem artichokes for rapid clonal propagation [13,14], microtuber induction [15], germplasm cryopreservation [16], inulin production [15], seed dormancy breaking [6], and genetic transformation [17]. Generally, callus induction is an important step in the in vitro regeneration protocols of many plants [18][19][20]. In the case of Jerusalem artichokes, researchers have shown that calli could be readily induced from tubers, leaves, and stem cuttings on MS basal medium supplemented with different types of plant growth regulators (PGRs) used in different concentrations [14,17,21,22].…”
Section: Introductionmentioning
confidence: 99%